Ratatouille - Pixar (Firm); Walt Disney Pictures (new york GENERAL AUDIIENCES, 2007)
A rat named Remy dreams of becoming a great chef despite his family's wishes and the obvious problem of being a rat in a decidedly rodent-phobic profession. When fate places Remy in Paris, he finds himself ideally situated beneath a restaurant made famous by his culinary hero. Despite the apparent dangers of being an unwanted visitor in the kitchen of one of Paris' most exclusive restaurants, Remy forms an unlikely partnership with Linguini, the garbage boy, who inadvertently discovers Remy's amazing talents. They strike a deal, ultimately setting into motion a chain of extraordinary events that turns the culinary world of Paris upside down
Title from container
1
Keywords: Feature films; Rats -- France -- Paris -- Drama; (3eGdJj ejOjG CWaGds -- (3ehGO SeYjI hHUQjIs